Lipoprotein‐Like Nanoparticle Carrying Small Interfering RNA Against Spalt‐Like Transcription Factor 4 Effectively Targets Hepatocellular Carcinoma Cells and Decreases Tumor Burden. Issue 5 (16th March 2020) - Cruz, William; Huang, Huang; Barber, Brian; Pasini, Elisa; Ding, Lili; Zheng, Gang; Chen, Juan; Bhat, Mamatha
Abstract : Patients with advanced hepatocellular carcinoma (HCC) are often unable to tolerate chemotherapy due to liver dysfunction in the setting of cirrhosis. We investigate high‐density lipoprotein (HDL)‐mimicking peptide phospholipid scaffold (HPPS), which are nanoparticles that capitalize on normal lipoprotein metabolism and transport, as a solution for directed delivery of small interfering RNA (siRNA) cargo into HCC cells. Spalt‐like transcription factor 4 (SALL4), a fetal oncoprotein expressed in aggressive HCCs, is specifically targeted as a case study to evaluate the efficacy of HPPS carrying siRNA cargo. HPPS containing different formulations of siRNA therapy against SALL4 were generated specifically for HCC cells. These were investigated both in vitro and in vivo using fluorescence imaging. HPPS‐SALL4 effectively bound to scavenger receptor, class B type 1 (SR‐BI) and delivered the siRNA cargo into HCC cells, as seen in vitro . HPPS‐SALL4 effectively inhibited HCC tumor growth ( P  < 0.05) and induced a 3‐fold increase in apoptosis of the cancer cells in vivo compared to HPPS‐scramble. Additionally, there was no immunogenicity associated with HPPS‐SALL4 as measured by cytokine production. Conclusion : We have developed unique HDL‐like nanoparticles that directly deliver RNA interference (RNAi) therapy against SALL4 into the cytosol of HCC cells, effectively inhibiting HCC tumor growth without any systemic immunogenicity. This therapeutic modality avoids the need for hepatic metabolism in this cancer, which develops in the setting of cirrhosis and liver dysfunction. These natural lipoprotein‐like nanoparticles with RNAi therapy are a promising therapeutic strategy for HCC. Abstract : Patients with advanced HCC are often unable to tolerate chemotherapy due to liver dysfunction in the setting of cirrhosis. We herein investigate High‐density Lipoprotein (HDL)‐mimicking Peptide Phospholipid Scaffold (HPPS), nanoparticles that capitalize on normal lipoprotein metabolism and transport, as a solution for directed delivery of RNA interference (siRNA) cargo into HCC cells. Our HDL‐like nanoparticles effectively inhibit HCC tumor growth without any systemic immunogenicity and avoid the need for hepatic metabolism in this cancer that develops in the setting of cirrhosis and liver dysfunction. Therefore, these natural lipoprotein‐like nanoparticles with RNA interference therapy are a promising therapeutic strategy for HCC.